1998
DOI: 10.1116/1.590232
|View full text |Cite
|
Sign up to set email alerts
|

Localized interface states and the optical spectra of AlSb/InAs heterostructures

Abstract: The existence of localized states at InSb-like interfaces of AlSb/InAs superlattices is predicted using empirical pseudopotential calculations. These predictions are shown to be in agreement with those of ab initio pseudopotential calculations performed using the local density approximation of density functional theory, demonstrating the ability of the empirical approach to describe the microscopic features of the interface. The frequency dependence of the absorption coefficient is calculated for a series of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…Various forms of interfacial roughness can arise during growth of semiconductor heterostructures, such as dislocations, impurity defects and atomic intermixing between adjacent layers of different materials. Such deviations from the ideal have been found to bring about significant quantitative and qualitative changes to the optical spectra of heterostructures in previous studies [18,20,26,27]. In the present paper, however, we look at the possible interface bond types which can arise in a perfect GaSb/InAs-superlattice system by sequencing the shutter speed during epitaxy.…”
Section: Interface Signature and Ir Absorptionmentioning
confidence: 89%
See 2 more Smart Citations
“…Various forms of interfacial roughness can arise during growth of semiconductor heterostructures, such as dislocations, impurity defects and atomic intermixing between adjacent layers of different materials. Such deviations from the ideal have been found to bring about significant quantitative and qualitative changes to the optical spectra of heterostructures in previous studies [18,20,26,27]. In the present paper, however, we look at the possible interface bond types which can arise in a perfect GaSb/InAs-superlattice system by sequencing the shutter speed during epitaxy.…”
Section: Interface Signature and Ir Absorptionmentioning
confidence: 89%
“…As such, we should approach any conclusions on the dependence of detector characteristics on the interface chemistry with some caution. However, we would stress that in earlier work [26] in which we studied a more rigorous description of atomic potentials at the interfaces of antimonidebased superlattices, using ab initio methods, a comparison with EP calculations showed that the latter method provided an adequate description of the effects of different interface types. While we cannot assume that this result necessarily holds for the present superlattices, we believe that the work cited does lend further credibility to our present results.…”
Section: Interface Signature and Ir Absorptionmentioning
confidence: 96%
See 1 more Smart Citation
“…The system discussed below has been physically realized in periodic repetitions of nanosized layers of InAs and GaSb in which the interfaces contain either GaAs or InSb bonds that are foreign to both InAs or GaSb, leading to a reduction of symmetry and, thus, wavefunction mixing at interfaces [1][2][3]. The possibility of interface localization due to the presence of foreign bonds at the interfaces in a related system of alternating AlSb and InAs layers was studied earlier using atomistic pseudopotential calculations [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…[12] Indeed, this energy state at the InSb-like interface is known as the Tamm state. [39,40] According to the calculation result of Shen et al, [41] the value of the Tamm state is proportional to the thickness of the InSb-like interface. The extracted E 1 of both samples is comparable to the 40-meV conclusion.…”
Section: Optical Investigationmentioning
confidence: 99%